인간-기계 인터페이스 및 증강현실 기술의 항공운항 분야 적용 - 박형욱; 정준; 장조원; 주성현; 황영하; Park, Hyeong Uk; Chung, Joon; Chang, Jo Won; Joo, Seonghyeon; Hwang, Young Ha (한국항공운항학회지, 2019)
The primary objective of this paper is to introduce the application of Human-Machine Interface (HMI) and Augmented Reality (AR) technologies in flight operations. These include: self-check-in, baggage handling, airport security and surveillance, airport operations monitoring, In-Flight Entertainment and Connectivity (IFEC), cockpit design, and cabin crew support. This paper investigates the application status and development trends of HMI and AR technologies for airports and aircraft. These technologies can provide more efficient in-flight passenger service and experience by using AR devices. This paper also discusses the developments such as; the Integrated Control Application (ICA) for the IFEC interface, AR flight simulation training program using the fixed-based simulator, and the AR aircraft cabin interior concept test program. These applications present how HMI and AR techniques can be utilized in actual flight operations. The developed programs in this paper can be applied to their purpose within aircraft interiors and services to enhance efficiency, comfort, and experience.